If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = -2(x + -5) Reorder the terms: -5 + 3x = -2(x + -5) Reorder the terms: -5 + 3x = -2(-5 + x) -5 + 3x = (-5 * -2 + x * -2) -5 + 3x = (10 + -2x) Solving -5 + 3x = 10 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -5 + 3x + 2x = 10 + -2x + 2x Combine like terms: 3x + 2x = 5x -5 + 5x = 10 + -2x + 2x Combine like terms: -2x + 2x = 0 -5 + 5x = 10 + 0 -5 + 5x = 10 Add '5' to each side of the equation. -5 + 5 + 5x = 10 + 5 Combine like terms: -5 + 5 = 0 0 + 5x = 10 + 5 5x = 10 + 5 Combine like terms: 10 + 5 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 3(x+1)=-2x+32 | | 3.62+5g=25.07 | | 4(2x+3)=3x+3+2x | | 7y=5y+22 | | -7(-9m-39)=-2(21-21m) | | -8x+5y=0 | | 5x+10-9=3(x+3) | | 7(9s-5)=8(8s-1)-12 | | 5x-15=5(x-5) | | 8.5z-8.7z-14=-18.5z-4(-5.9z-8.16) | | [x+5]=0 | | 16-3x+8=3-4x+8 | | -5(1-8a)+1=116 | | 40=1/2(-9.8)t^2 | | 20-4K=3(k+2) | | 87+94y-2=-6(-16y-27)+6 | | 10x-27=20 | | (x-2)(x+1)=(2x-5)+1 | | 3[4x+3]=2x-5[3-x]+2 | | a^2-2ax+x^2-9=0 | | -9(-2q-73)-83q=8(-8q+65) | | 2(4x+7)=5x+44 | | 8*x+9=33 | | 10+6x=-6x-50 | | [(2x+5)+3y][(2x+5)-3y]=0 | | 14.5=5n-2 | | 8x+6+2x=12+4x | | 4x-8=8x+7-7x | | 5(-17c+53)=-7(5c-45) | | 120=x | | 121=-8m+7(1-7m) | | -10-1=7x-5-x |